Some insights into an integrative mathematical model:: a prototype-model for bodyweight and energy homeostasis - Pires, Jorge Guerra (Revista Gestão & Saúde, 2016)
The ambition of this document is to set in evidence the prerequisite for integrative (mathematical) models, mechanism-based models, for appetite/bodyweight control. For achieving this goal, it is provided a scrutinized literature review and it is organized them in such a way to make the point. The quantitative methods exploited by the authors are called differential equations solved numerically; they are discussed briefly since it is not our goal herein to handle details. On the current state of the art, there is no mathematical model to the best of the author’s knowledge targeting at integrating several hormones at once in mathematical descriptions: even for single hormones, the literature is either occasional or do not exist at all; it is depicted some results for simple models already built. As it can be seen, the functions and roles seem fuzzy, most hormones seem to be piloting the same undertaking. The key challenge from a mathematical modeling perspective is how to separate properly the mechanisms of each hormone. The kind of pursuit presented herein could initiate an imperative cascade of mathematical modeling applied to metabolism of bodyweight control and energy homeostasis.